Rethinking the Pedagogical Role of Primary Education Teachers at the UNED Basic General Education Program (Cycles I and II) - Palma Rojas, Karen (2025)
When the Bachelor’s Degree Program in Basic General Education at the State Distance University of Costa Rica (UNED) embarked on revising its curriculum in 2021, it faced the challenge of rethinking the pedagogical role of primary school teachers. The objective was to provide a fresh viewpoint to the field that went beyond conventional methods and give a contemporary purpose their daily activities. The process began by examining contemporary societal perceptions about primary school teachers followed by research into current and emerging teacher-training trends. Given the multidisciplinary nature of teaching, the study explores the contributions that science has made to the profession. This was accomplished through an in-depth targeted scientific literature review. Due to the breadth and complexity of the matter, the study addresses how the role of primary school teachers has evolved subject over time, from its foundation in colonial times to more recent changes in education policies. It looks at the curriculum and the establishment of the National Qualifications Framework for Professional Training, the trends and demands that evolved and the academic disciplines that served as the foundation for changes in teacher-training. The information was organized by tables to simplify analysis and understand the underlying theory. This process led to an innovative concept that regards teachers in the first and second cycles of basic general education (EGB) (grades 1-6) as managers of “inclusive educational settings that promote learning, skills, and the comprehensive development of primary school students” (Palma & Mesén, 2022, p. 359). Primary school teachers are experts in primary education since they carry out a broad range of complex tasks and are able to manage these responsibilities in inclusive classrooms. They perceive their job as teachers as an opportunity to transform and empower their students by responding to the needs of their school and our modern world.